The effects of sodium-glucose cotransporter-2 inhibitors in chemotherapy-induced cardiotoxicity and mortality in patients with cancer: a systematic review and meta-analysis - Tara Reshadmanesh; Reza Mohebi; Amir Hossein Behnoush; Azadeh Reshadmanesh; Amirmohammad Khalaji; Mitra Norouzi; Elmira Javanmardi; Reza Pishdad; S. Reza Jafarzadeh; Elina Ghondaghsaz; Sandra Chaparro (Cardio-Oncology)
Abstract Background The effects of sodium-glucose cotransporter-2 (SGLT2) inhibitors on reducing cardiovascular events in different subgroups of diabetic patients are under investigation. The current systematic review and meta-analysis investigated the effects of SGLT2 inhibitors on preventing cardiovascular events and mortality and their adverse events in patients with active cancer and diabetes undergoing cardiotoxic cancer treatment. Methods We searched PubMed, Embase, Web of Science, and Scopus to find studies investigating the effects of SGLT2 inhibitors on patients with diabetes and confirmed cancer until 19 August 2024. Meta-analyses were conducted using the random-effects model to compare all-cause mortality, cancer-associated mortality, heart failure (HF) hospitalization, arrhythmia, and adverse event rates such as ketoacidosis, hypoglycemia, urinary tract infection, and sepsis between patients with or without SGLT2 inhibitors use. Risk ratios (RRs) with 95% confidence intervals (CI) were used to compare outcomes between SGLT2 inhibitors and non-SGLT2 inhibitors groups. Results Eleven studies were included with 88,096 patients with confirmed cancer (49% male). Among the total population, 20,538 received SGLT2 inhibitors (age 61.68 ± 10.71), while 67,558 did not receive SGLT2 inhibitors (age 68.24 ± 9.48). The meta-analysis found that the patients who received SGLT2 inhibitors had a significantly lower mortality rate than those who did not receive SGLT2 inhibitors (RR 0.46, 95% CI 0.34 to 0.63, p-value < 0.0001). Similarly, the cancer-associated mortality rate was also lower (RR 0.29, 95% CI 0.27 to 0.30, p-value < 0.0001). Further analysis found that the SGLT2 inhibitor group had a lower rate of HF hospitalization, compared to controls (RR 0.44, 95% CI 0.27 to 0.70, p-value = 0.0007). Moreover, patients receiving SGLT2 inhibitors had a statistically lower rate of arrhythmia (RR 0.38, 95% CI 0.26 to 0.56, p-value < 0.0001). Finally, patients in the SGLT2 inhibitors group had a lower rate of adverse events (RR 0.51, 95% CI 0.42 to 0.62, p-value < 0.0001). Conclusions SGLT2 inhibitors are effective in reducing mortality (all-cause and cancer-associated), HF hospitalization, arrhythmia, and drug adverse events in patients with cancer. If confirmed in future studies, these agents could be a potentially ideal candidate to prevent cardiotoxicity of cancer therapies.